Screening of Antioxidant Activities in Gonad Extracts of Stomopneustes variolaris - Arockia Vinista, S. Motch; Hermelin Jesy Diaz, Jemma (Journal of Neonatal Surgery, 2026)
The present study investigated the in-vitro antioxidant potential of Stomopneustes variolaris using aqueous, chloroform, and methanolic gonad extracts at a concentration of 200 µg/mL. Antioxidant activity was evaluated through 2,2-diphenyl-1-picrylhydrazyl (DPPH) radical scavenging assay, hydrogen peroxide (H₂O₂) scavenging assay, and total antioxidant capacity (TAC) assay. Among the tested extracts, the methanolic extract exhibited the highest antioxidant activity with 61% DPPH radical scavenging activity, 44% H₂O₂ scavenging activity, and 57% total antioxidant capacity. The chloroform extract demonstrated moderate antioxidant potential with 55% DPPH activity, 35% H₂O₂ scavenging, and 40.19% TAC, while the aqueous extract showed the lowest activity of 36.12% DPPH 22% H₂O₂, and 31.23% TAC respectively. The findings indicate that the methanolic extract of S. variolaris possesses significant antioxidant potential, due to the higher extraction efficiency of bioactive antioxidant compounds in methanol. These results suggest that S. variolaris may serve as a promising natural source of antioxidant compounds for potential pharmaceutical and nutraceutical applications.